An Extended Rheological Map of Pāhoehoe—'A'ā Transition. Issue 7 (8th July 2021) - Di Fiore, F.; Vona, A.; Kolzenburg, S.; Mollo, S.; Romano, C.
Abstract: The pāhoehoe—'a'ā morphological transition involves a change in the rheological response of the magmatic suspension from pure viscous to complex rheological behavior, resulting in the development of tear‐apart features. Here, we present a suite of concentric cylinder experiments aimed at studying the effects of cooling and shear rates on the rheology of a phonotephrite melt in response to crystallization. Experiments were conducted at: (a) isothermal subliquidus temperatures of 1, 167–1, 189°C and shear rates of 1–3 s −1 ; (b) constant cooling rates of 1–10°C/min and shear rates of 1–20 s −1 . We defined the viscosity‐temperature‐time window of lava solidification, as well as the transition from coherent flow to shear localization and physical separation (i.e., viscous rupture). Through this approach, we mapped the processes and timescales affecting pāhoehoe—'a'ā transition in natural lavas at variable cooling and shear rates. Under disequilibrium conditions, as the cooling rate increases, both crystallization onset and viscous rupture occur at lower temperature and earlier in time. Moreover, the time to reach the crystallization onset and viscous rupture also decreases with increasing shear rate. Both increasing cooling and shear rate reduces the critical crystallinity required for viscous rupture, a consequence of the non‐linear interplay between temperature, crystallization kinetics, and melt viscosity. This outcome expands our knowledge on compositional, thermal, and rheological changes in phonotephritic systems. In addition to shear rate and apparent viscosity, comparison with previous measurements on basaltic systems indicates that the pāhoehoe—'a'ā transition is sensitive to the composition and cooling path of lavas. Plain Language Summary: During flow on Earth's surface, mafic lava frequently undergo changes in their surface morphology, with transition from smooth and continuous (pāhoehoe) surfaces to rough and fragmental ('a'ā) aspects. This morphological transition is the result of changes in the lava's deformation style (i.e., rheology) as a response to flow. It affects both lava flow geometry and the efficiency of heat loss—ultimately governing lava advance rates and distances. Therefore, our ability to model and forecast lava emplacement and related hazards relies on knowledge of the lava's syn‐eruptive rheological evolution. We present an experimental study on the effect of deformation and cooling rate on the crystallization dynamics and rheology of a melt from Mt. Vesuvius (Italy). Combination of different experimental approaches (i.e., isothermal and cooling deformation experiments), enables measurements of the rheological evolution of the melt during crystallization. The resulting data track the transition in deformation style from coherent flow (pāhoehoe lavas) to surface rupture ('a'ā lavas) and provide the first systematic map of the pāhoehoe—'a'ā transition under variable cooling and deformation regimes. This has implications for the understanding and modeling of lava flow hazards and support strategies to mitigate volcanic risks. Key Points: High‐T deformation experiments explore the rheology of a phonotephrite melt under both equilibrium and disequilibrium conditions Crystallization is enhanced by decreasing cooling rate and/or increasing shear rate Rheological data identify and map the pāhoehoe—'a'ā transition, controlled by composition, shear rate, and cooling path of lavas